The karyology and taxonomy of the southern African yellowfish (Pisces : cyprinidae) - Oellermann, Lawrence Keith (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1989)
The southern African yellowfish (Barbus aeneus, B. capensls, B. kimberleyensis, B. natalensis and B. polylepis) are very similar, which limits the utility of traditional taxonomic methods. For this reason yellowfish similarities were explored using multivariate analysis and karyology. Meristic, morphometric and Truss (body shape) data were examined using multiple discriminant, principal component and cluster analyses. The morphological study disclosed that although the species were very similar two distinct groups occurred; B. aeneus-B. kimberleyensis and B. capensis-B. polylepis-B. natalensis. Karyology showed that the yellowfish were hexaploid, B. aeneus and B. kimberleyensis having 148 chromosomes while the other three species had 150 chromosomes. Because the karyotypes of the species were variable the fundamental number for each species was taken as the median value for ten spreads. Median fundamental numbers were B. aeneus = 196, B. natalensis = 200, B. kimberleyensis = 204, B. polylepis = 206 and B. capensis = 208. The lower chromosome number and higher fundamental number was considered the more apomorphic state for these species. Silver-staining of nucleoli showed that the yellowfish are probably undergoing the process of diploidization. Southern African Barbus and closely related species used for outgroup comparisons showed three levels of ploidy. The diploid species karyotyped were B.anoplus (2N=48), B. argenteus (2N=52), B. trimaculatus (2N=42-48), Labeo capensis (2N=48) and L. umbratus (2N=48); the tetraploid species were B. serra (2N=102), B. trevelyani (2N=Â±96), Pseudobarbus afer (2N=96) and P. burgi (2N=96); and the hexaploid species were B. marequensis (2N=130-150) and Varicorhinus nelspruitensis (2N=130-148). The taxonomic implications of polyploidy for the African cyprinids were considered, and its effect on species was discussed.
Keywords: Barbus -- South Africa; Cyprinidae -- South Africa